Constitutive Expression of Candida antarctica Lipase B (CALB) in Pichia pastoris Using pGAPZα Vector - Wahyuni, Febriana Dwi; Fuad, Asrul Muhamad; Suharsono, Suharsono (Annales Bogorienses, 2016)
The synthetic gene of CalBsyn was previously constructed to encode Candida antarctica lipase B (CALB). Lipase of CalBsyn gene is slightly different from wild type CALB (CALB-wt) where it has three amino acids substitutions at different positions, i.e. V210I, A281E, and V221D, in order to improve its thermostability and catalytic efficiency. The CalBsyn gene was isolated from pJ912-CalBsyn vector by digestion using XhoI restriction enzyme. The 1136 bp fragment of CalBsyn gene was then ligated to pGAPZα expression vector and transformed into Escherichia coli TOP10F’ to obtain recombinant vector pGAPZα-CalBsyn. The result show that pGAPZα-CalBsyn recombinant vector was successfully transformed into E. coli TOP10F’ with transformation efficiency of 4.11x103 cfu/μg plasmid DNA. The pGAPZα-CalBsyn recombinant plasmid was successfully introduced into Pichia pastoris SMD1168H using electroporation method with transformation efficiency of 1.01x102 cfu/μg DNA. Recombinant protein expression was analyzed in several selected P. pastoris recombinant strains. Qualitative lipase activity assays results show that transformed P. pastoris-produced extracellular recombinant lipase (CALB) showing lipolytic activity; while results of quantitative lipase activity assays show that this Pichia-derived lipase achieved an activity of 6.35 Units/mL within 48 hours. SDS-PAGE analysis confirms the succesfull expression of CALB protein with molecular size was approximately 45 kDa.